Analysis of distant cardiovascular events depending on the biomarker profile in patients with myocardial infarction - A. F. Khamitova; Sh. Z. Zagidullin; I. R. Lakman; D. F. Gareeva; N. Sh. Zagidullin (Российский кардиологический журнал)
Acute coronary syndrome (ACS) and its complications is one of the main reasons of mortality and invalidation in the world. New biomarkers, such as ST2, NT-proBNP и Pentraxin-3 (Ptx-3) present much more opportunities in the diagnostics of diseases and risk of its development.Aim. To investigate standards and “new” biomarkers in different variants of MI and cardiovascular events in 1 year after MI.Material and methods. In 180 patients with MI (61,4±1,7 years) we determined the serum concentration of standard and “new” (ST2, NT-proBNP, Ptx-3) biomarkers in groups with Q/non-Q, STEMI and NSTEMI and the endpoints (MI, strokes, repeated hospitalizations and sudden deaths) in 1 year (384,3±21,2 days) after MI.Results. Patients with Q-MI and STEMI had higher risk of unfavorable cardiovascular events (p<0,05). Ptx-3 >43,9 ng/ml was shown to be risk factor for sudden death (sensitivity 70,0%, specificity 52,9%), and >125,9±0,06 ng/ml (74,1% and 44,1%) — of recurrent MI.Conclusion. NT-proBNP, ST2 and Ptx-3 showed prognostic value in the diagnostics of unfavorable cardiovascular endpoints.